A Comparison of the Mental Health and Well-Being of Sexual Minority and Heterosexual First-Year Medical Students: A Report From the Medical Student CHANGE Study. (May 2015) - Przedworski, Julia M.; Dovidio, John F.; Hardeman, Rachel R.; Phelan, Sean M.; Burke, Sara E.; Ruben, Mollie A.; Perry, Sylvia P.; Burgess, Diana J.; Nelson, David B.; Yeazel, Mark W.; Knudsen, John M.; van Ryn, Michelle
Abstract : Purpose: Research is lacking on psychological distress and disorder among sexual minority medical students (students who identify as nonheterosexual). If left unaddressed, distress may result in academic and professional difficulties and undermine workforce diversity goals. The authors compared depression, anxiety, and self-rated health among sexual minority and heterosexual medical students. Method: This study included 4, 673 first-year students who self-reported sexual orientation in the fall 2010 baseline survey of the Medical Student Cognitive Habits and Growth Evaluation Study, a national longitudinal cohort study. The authors used items from published scales to measure depression, anxiety, self-rated health, and social stressors. They conducted bivariate and multivariate analyses to estimate the association between sexual identity and depression, anxiety, and self-rated health. Results: Of 4, 673 students, 232 (5.0%) identified as a sexual minority. Compared with heterosexual students, after adjusting for relevant covariates, sexual minority students had greater risk of depressive symptoms (adjusted relative risk [ARR] = 1.59 [95% confidence interval, 1.24–2.04]), anxiety symptoms (ARR = 1.64 [1.08–2.49]), and low self-rated health (ARR = 1.77 [1.15–2.60]). Sexual minority students were more likely to report social stressors, including harassment (22.7% versus 12.7%, P < .001) and isolation (53.7% versus 42.8%, P = .001). Exposure to social stressors attenuated but did not eliminate the observed associations between minority sexual identity and mental and self-reported health measures. Conclusions: First-year sexual minority students experience significantly greater risk of depression, anxiety, and low self-rated health than heterosexual students. Targeted interventions are needed to improve mental health and well-being. Abstract : Supplemental Digital Content is available in the text.